'We wouldn't be boys if we weren't clever with our hands' – childhood masculinity in a rural community in Norway. Issue 1 (2nd January 2017) - Stordal, Gjertrud
ABSTRACT: This article aims to contribute to the growing body of knowledge about the relations between gender and rurality by looking at how boys in a rural community in Norway construct masculine identities. Data were generated through interviews with 18 boys aged 8–10 years, in groups and individually. The analysis focuses on how the boys construct masculinities in a process that is embedded in the generational condition of being children within a rural community. In the interviews, talk about manual labour and practical knowledge is central to the construction of childhood masculinities among the boys, a gender identity through which the boys create a sense of interdependence and belonging to the community. Alternative and more subversive constructions of masculinity related to school achievements, care, and housework challenge the hegemony of practical knowledge, and provide potential for change and transgressions towards more flexible and multiple constructions of masculinities among the boys. This article provides knowledge about the interrelation between notions of childhood and rural masculinity, and point to the importance of considering the boys active participants and social agents in rural life.